PENERAPAN MODEL PENDIDIKAN KARAKTER BERBASIS ECOPEDAGOGY DI SD NEGERI TAMAN KALIJAGA PERMAI - Ariskayanti, Velen; Nur Jannah, Widia; Faiz, Aiman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Based on environmental problems that are increasing day by day, and this is closely related to human behavior. This study aims to describe the application of the ecopedagogy-based character education model as an effort to instill the value of environmental care at SD Negeri Taman Kalijaga Permai. The type of research used is qualitative research with descriptive methods using observation, interviews, and documentation as data collection techniques. The results showed that through the planning, process, and evaluation of the ecopedagogy-based character education model carried out, it can help students develop the character of environmental care, environmental awareness, and skills in environmental conservation. This is shown through the behavior of students who are able to form a combination of environmental care and responsibility values into a value system that is used as a guide for each individual at school by carrying out activities to process waste into usable goods, consistently bringing food and drink containers from home, and maintaining plants.